Investigating the catalytic properties of hydroxyapatite derived from mussel shells for the treatment of wastewater - Jun Haslinda, Haji Shariffuddin (2015)
The seafood processing industry in New Zealand and worldwide generates a large amount of shell waste and currently the shell waste under-utilized. The possibility of producing a useful product from this shell wastes will greatly enhance and ensure sustainable economic development as well as the associated waste management problems. Therefore, as one possible solution, the overall objective of this study was to investigate the feasibility of mussel shells waste for the synthesis of hydroxyapatite, CaiO(P04)6(0H)2 (denoted as HAP) and other derivatives from mussel shells to act as photocatalyst in degradation of methylene blue and dehydroabietic acid in aqueous media via photocatalysis.